"Live high-train low" induced changes in hemoglobin mass and the erythropoietin-erythroferrone-hepcidin axis in female endurance athletes - Kuorelahti, T.; Ihalainen, J. K.; Linnamo, V.; Badenhorst, C.; Kettunen, O.; Mikkonen, R. (Physiological Reports, 2025)
The effects of a 21-day live high-train low (LHTL) on hemoglobin mass (Hbmass) and iron demand including the erythropoietin (EPO)-erythroferrone (ERFE)-hepcidin axis and routine iron markers were investigated. Fifteen female endurance athletes completed either 21-day LHTL in normobaric hypoxia (2500 m, ~18 h·day-1) (INT, n = 8) or lived and trained in normoxia (CON, n = 7). Hbmass and resting blood were collected before and after the intervention. An additional blood sample was collected on Day 6 for INT. 21-day LHTL increased Hbmass 3.8% in INT (p < 0.001). EPO increased 35.6% from Day 0 to Day 6 in INT (p = 0.037) and then decreased 42.4% from Day 6 to Day 21 (p = 0.019). In INT, no changes were detected in ERFE or hepcidin, and from the routine iron markers only serum transferrin receptor increased from Day 0 to Day 21 (13.9%, p = 0.013). In CON, no changes were detected in Hbmass or iron markers. In INT, Hbmass and ferritin were positively associated (Day 0 to Day 6, p = 0.005). Thus, hepcidin and ERFE may not provide additional information regarding iron demand following 6- or 21-day LHTL compared to routine iron markers. The relationship between Hbmass and ferritin indicates that adequate ferritin levels are needed during hypoxia to support hematological adaptations.